The Effect of Habits of Mind on Students' Reasoning Ability through Mathematic Connections - Indriani, Tari; Retnawati, Heri (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Students often have trouble developing their math reasoning skills to the fullest because they don't have the habit of thinking reflectively and don't have strong connections between math concepts. This problem shows the need for learning that can systematically integrate habits of mind and mathematical connections into students' thinking processes. This study aims to analyze in depth the direct and indirect effects of habits of mind on mathematical reasoning skills through students' mathematical connections in 10th grade high school. This is a quantitative study with an ex-post facto design. The research subjects consist of 342 students as the main sample. Data were collected using instruments in the form of a mathematical connection ability test, a mathematical reasoning ability test, and a habits of mind questionnaire. The instruments underwent content validity testing, reliability testing, and item characteristic analysis using Confirmatory Factor Analysis and Item Response Theory. The data analysis techniques used were regression analysis and path analysis to examine the causal relationships between variables directly and indirectly. The analysis results indicate a significant direct effect of habits of mind on students' mathematical connection abilities. The findings of this study suggest that habits of mind play a crucial role in enhancing students' mathematical reasoning abilities indirectly through the strengthening of mathematical connections. This finding underscores the importance of integrating affective and cognitive aspects in mathematics education. The implications of this study are that teachers need to design learning strategies that can foster habits of mind.